COMPARISON OF LEFT CORONARY ARTERY DIAMETER AMONG DIABETICS AND NON-DIABETICS - ., Faridullah; Adil, Muhammad; Nadeem, Muhammad; Hafizullah, Mohammad; Jan, Hikmatullah (Journal of Postgraduate Medical Institute, 2012)
Objective: To compare the left coronary artery diameter between diabetic and non-diabetic patients undergoing coronary angiography. Methodology: This was a hospital based cross sectional comparative study. After obtaining an informed consent, 139 patients each in diabetic and non-diabetic groups were selected by non-probability purposive sampling method. Coronary angiography was done through femoral approach using Seldeinger technique and standard views were taken. Quantitative analysis of digital angiograms was performed. Data analyzed using SPSS version 11.0. Independent t test was applied to calculate mean coronary artery size between diabetic and non-diabetic patients. A p-value of less than 0.05 was considered significant. Results: Out of 278 patients included in the study, 139 (50%) were diabetics and 139 (50%) were nondiabetics. Males were 168 (60.4%) as compared to females 110(39.6%). Mean age was 52.82 + 7.115, and mean body surface area was 1.8004 +.11094. There was significant difference in coronary diameters of LAD (p value 0.000), LMS (p value 0.008), and distal Cx coronary arteries (p value 0.000) between the two groups. Conclusion: In this study, left coronary arteries and its branches were found to be narrower in diabetic patients than in non-diabetics.